Early Postoperative Outcomes of Endoscopic Versus Open Vein Harvesting of Great Saphenous Vein in On-Pump Coronary Artery Bypass Grafting - Rameez, S.M. Ammar; Asghar, Muhammad Imran; Janjua, Asif Mahmood; Khan, Muhammad Ahmad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare early leg wound complications, cosmetic satisfaction, between Endoscopic Vein Harvesting technique (EVH) and open vein Harvesting (OVH) in Coronary Artery Bypass Graft (CABG) surgery patients. Study Design: Quasi Experimental Design Place and Duration of Study: Department of Adult Cardiac Surgery, Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, Jan 2025- Nov 2025. Methodology: Thirty elective on pump CABG patients with ≥ 18 years regardless of gender were enrolled. Patients were divided into two groups, Group-EVH (n = 15) and Group-OVH (n = 15), non-randomly. Baseline demographics, intraoperative parameters, and post-operative outcomes, including pain at discharge, wound complications (hematoma, edema, drainage, infection, and wound dehiscence), ASEPSIS scores, Euro quality of life and cosmetic satisfaction, were recorded and compared between the groups. Results: The mean age of the 30 patients was 54.03±10.85 years, with 20(66.7%) males and 10(33.3%) females. Age, BMI, gender, ejection fraction, and number of grafts were comparable between the groups (p>0.05). EVH demonstrated significantly lower post-operative wound complications, ASEPSIS scores, leg pain at discharge (mild pain: 40% versus 0% and severe pain: 33% versus 67%; p < 0.05), and improved cosmetic satisfaction (80% versus 26.7%) compared to OVH. EVH had a longer vein harvesting time compared to OVH (40.0 ± 12.47 min versus 20.4 ± 2.66 min; p = 0.001 respectively). Conclusion: EVH is a less invasive, safe, and practical substitute for OVH that offers greater post-operative quality of life, less pain, less wound problems, and enhanced cosmetic pleasure.